(untitled) (Scientific journal of the Fergana State University, 2024)
This article is of interest because today, more than ever, researchers are paying attention to the problem of the connection between language and culture, their interdependence and mutual influence. The paper examines language categories, concepts, and the relationship between language and culture from the point of view of philological comparative studies. Special attention is paid to linguistic signs that perform the function of the "language" of culture, which is expressed in the ability of the language to reflect the cultural and national mentality of its speakers.